Exploring the Facets of Empathy and Pain in Clinical Practice: A Review. Issue 8 (25th February 2017) - Roche, Jenny; Harmon, Dominic
Abstract: Background: Empathy is an essential element in providing quality patient care. The significance of empathy is even more striking in pain medicine, as chronic pain is notorious for the way it can compromise an individual, leaving him or her isolated and feeling misconceived. This review examines the role of empathy in pain medicine practice. Methods: Current and past literature focusing on empathy and pain was searched for in PubMed, Science Direct, MEDLINE (Ovid), MEDLINE (Ebsco), Research Gate, and Google Scholar in July 2015. Search dates were not limited and languages included English only. Search terms were "empathy and pain, " "empathy and chronic pain, " "physician empathy and pain, " "neural mechanisms and empathy, " "empathy in clinical practice, " "empathy and stigma, " and "empathy and medical students". To select relevant publications, the title and abstract of every publication were examined, and when in doubt, the rest of the publication was read. Results: Four major themes were identified: (1) the neural basis for empathy and pain; (2) the value and challenges of practicing empathy pain medicine; (3) stigma and empathy for pain; and (4) empathy and physician education and training. Conclusion: The review reveals that empathy deserves an unchallenged place in medical care, especially in pain medicine and medical education. It highlights the need to nurture empathy at all levels of professional expertise from medical student to senior doctors.